Uji Kinerja Turbin Turgo dengan Variasi Jumlah Sudu dan Sudut Kemiringan Nozzle - La Ode Musa; Jamal Jamal; Ridwan Ridwan; Intania Namira Luspa (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
Electrical energy is energy that has an important role for society. A number of ways have been done to meet electricity needs, one way is by using various alternative energy sources. These alternative energy sources include: Water, Wind, and Solar. But water is a cheap and relatively easy source of energy. So we need a tool that is used to convert the water energy into electrical energy, one of which is a turbine. This turbine will utilize the energy of fluid flow into mechanical energy, which will then be converted into electrical energy. In this study, we designed a turgo turbine model using a stainless steel spoon as the blade. By varying the number of blades and the angle of inclination of the nozzle. The methods used are literature studies, design methods, manufacturing methods, testing methods, and data analysis methods. Based on the test results, the 15 blade variation has an average efficiency of 3.65%. For the variation of the 20 blade has an average efficiency of 4.50%. And the 25 blade variation has an average efficiency of 4.90%. As for the variation of the 0° angle, the average efficiency is 2.84%. For the 15° angle variation the average efficiency is 4.80%. For the 25° angle variation the average efficiency is 5.45%. And for the variation of the angle of 35° the average efficiency is 4.33%.